2006
DOI: 10.1186/1471-2350-7-64
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of polymorphisms in the 17q11.2-12 CC chemokine gene cluster for association with multiple sclerosis in Australians

Abstract: Background: Multiple sclerosis (MS) is a disorder of the central nervous system (CNS) characterised by inflammation and neuronal degeneration. It is believed to result from the complex interaction of a number of genes, each with modest effect. Chemokines are vital to the migration of cells to sites of inflammation, including the CNS, and many are implicated in MS pathogenesis. Most of the CC chemokine genes are encoded in a cluster on chromosome 17q11.2-12, which has been identified in a number of genome wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…CXCL10/IP-10, CCL2/MCP-1, CCL3/MIP-1a, CCL4/MIP-1b, CCL5/Rantes, CCL7/MCP-3 and CXCL9/Mig [ 11 25 ] are among the described proinflammatory chemokines produced by immune cells and CNS glia in MS and in the animal model of MS, experimental autoimmune encephalomyelitis (EAE). Most of the β-chemokines or CC chemokine ligands (CCL) genes are clustered in chromosome 17q11.2–12, a location that has been associated with MS in different studies [ 26 28 ]. In a model of EAE, increased levels of Eotaxin/CCL11 were associated with milder disease phenotype, tighter blood brain barrier, reduced antigenic specific response and an anti-inflammatory Th2 phenotype [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…CXCL10/IP-10, CCL2/MCP-1, CCL3/MIP-1a, CCL4/MIP-1b, CCL5/Rantes, CCL7/MCP-3 and CXCL9/Mig [ 11 25 ] are among the described proinflammatory chemokines produced by immune cells and CNS glia in MS and in the animal model of MS, experimental autoimmune encephalomyelitis (EAE). Most of the β-chemokines or CC chemokine ligands (CCL) genes are clustered in chromosome 17q11.2–12, a location that has been associated with MS in different studies [ 26 28 ]. In a model of EAE, increased levels of Eotaxin/CCL11 were associated with milder disease phenotype, tighter blood brain barrier, reduced antigenic specific response and an anti-inflammatory Th2 phenotype [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic polymorphisms in the homologous region on human chromosome 17 have been studied for involvement in MS susceptibility, [29][30][31][32] as well as other autoimmune or chronic inflammatory diseases including RA, 60 myocardial infarction 66,67 and allergy. 68 A second cluster including chemokine genes (CCL5, CCL16, CCL14, CCL15, CCL23, CCL18, CCL3 and CCL4) located further upstream has also been studied in relation to MS, but in this study we have focused on the centromeric cluster, as this was identified in the rat linkage study.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 There is evidence for a role of specific chemokines in regulation of disease and cell migration in both MS 26 and EAE. 27 The chemokine genes have also been included in linkage and association studies, [28][29][30][31] but despite substantial evidence for linkage and association to this chemokine cluster, data lack conclusive replication. 32 In this study, we refine the Eae18b locus to a 0.88 Mb region containing the chemokine gene cluster and show that the expression of chemokines Ccl2, Ccl11 and Ccl1 is regulated by the locus.…”
Section: Il7rmentioning
confidence: 99%
“…Most chemokine genes are encoded in a cluster on chromosome 17q11.2-12, which has been identified in a number of genome-wide screens as being potentially associated with MS (15). Polymorphism of CCR2, IL-10 receptor α, and Fas-L may confer protective effects for MS; and polymorphism of CCR5, IL-10, IL-4 receptor α, IL-2 receptor ß, IFN-γ, vitamin D, and estrogen receptor confer risk to MS (1).…”
Section: Ccr5-δ32 Genetic Polymorphism Associated With Benign Clinicamentioning
confidence: 99%